2022
DOI: 10.1039/d2cc02882d
|View full text |Cite|
|
Sign up to set email alerts
|

Catalytic (3 + 2) umpolung annulations of α-thioacyl carbenes with aryl isothiocyanates

Abstract: 1,2,3-Thiadiazoles serve as masked S-electrophilic thia-1,3-dipoles. Under rhodium/racemic BINAP catalysis they undergo denitrogenative (3 + 2) umpolung transannulations with aryl isothiocyanates with inverse regioselectivity and excellent stereoselectivity, yielding N-aryl 3H-1,2-dithiol-(Z)-3-imines...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Transition metal-catalyzed denitrogenative transformations of 1,2,3-thiadiazoles have been demonstrated to be a facile and highly efficient approach to access structurally diverse heterocycles, [1][2][3] including thiophenes, [4][5][6][7][8] thiazoles, 9 isothiazoles, [10][11][12] 4H-thiopyran-4-ones, 13 thiochromenones, 14 1,3-thiaphospholes 15 and furans. 7,16 The mechanism of denitrogenative 1,2,3-thiadiazole transannulation reactions was investigated by Bao in 2021 using density functional theory (DFT) calculations, 17 with the structure of the key cyclometalated Rh(III) intermediate recently confirmed by our group using crystallographic data.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal-catalyzed denitrogenative transformations of 1,2,3-thiadiazoles have been demonstrated to be a facile and highly efficient approach to access structurally diverse heterocycles, [1][2][3] including thiophenes, [4][5][6][7][8] thiazoles, 9 isothiazoles, [10][11][12] 4H-thiopyran-4-ones, 13 thiochromenones, 14 1,3-thiaphospholes 15 and furans. 7,16 The mechanism of denitrogenative 1,2,3-thiadiazole transannulation reactions was investigated by Bao in 2021 using density functional theory (DFT) calculations, 17 with the structure of the key cyclometalated Rh(III) intermediate recently confirmed by our group using crystallographic data.…”
Section: Introductionmentioning
confidence: 99%
“…Yang group reported a Rh catalyzed [3 + 2] umpolung annulations of α-thioacyl carbenes derived from 1,2,3-thiadiazoles ( 77 ) with aryl isothiocyanates ( 78 ). 40 The reaction proceeded in umpolung, stereospecific, and regiospecific manner as more nucleophilic CS serves as the reactive site instead of the less nucleophilic CN bond of the isothiocyanate. On the other hand, 1,2,3-thiadiazoles act as masked S -electrophilic, thia-1,3-dipoles in this Rh-catalyzed redox-neutral [3 + 2] annulations.…”
Section: Reactivity Of Alkyl/aryl Itcsmentioning
confidence: 99%
“…demonstrated that 1,2,3-thiadiazoles 132 can undergo denitrogenative transannulation with isothiocyanates 133 under Rh(I)/(�)-BINAP catalysis in the presence of CsI as an additive (Scheme 21a). [39] Similar to nitriles, in the presence of isothiocyanates, thiadiazoles 132 have been observed to exhibit inversed (umpolung-type) reactivity as masked S-electrophilic 1-thia-1,3-dipoles, affording 1,2-dithiapent-3-enes 134 exclusively, in a regiospecific and stereospecific fashion. Generally, the developed reaction has been demonstrated to have broad substrate scope and functional group compatibility, however, 1,2,3-thiadiazoles 135-140 were unsuccessful (Scheme 21b), and only aryl-substituted isothiocyanates were effective.…”
Section: Rhodium(i)-catalyzed Denitrogenative Annulation Reactions Of...mentioning
confidence: 99%